Planning and Implementing Smart Shrinkage of Rural China: The Case of Chengduâs Rural Settlement Consolidation with SGME Model - Lie You; Chen Chen (The Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
Accompanying Chinaâs fast urbanization, a paradox arises as rural China is decreasing in population but rural settlements are still expanding in the form of rural housing renovation and increased construction land, especially in migrant-sending areas. The urban-rural dual system in China is blamed as the main cause of this abnormal phenomenon, but as the dual system is fundamental to Chinaâs socio-economic development and Chinaâs central government adopts institutional reform in a step-by-step fashion, local governments have to work around this dual system. Many municipalities are planning and implementing smart shrinkage of rural settlements and Chengdu is among the best practices in the Chinese context. This research describes the latest SGME (small-scale settlement, group arrangement, micro pastoral scenery and ecological construction) model, which was initiated in 2013 to implement planned consolidation of rural settlements that fits the local development culture. In order to better allocate public service facilities and improve the efficiency of resource supply, six modes of spatial agglomeration are planned to consolidate villages scattered all over Chengdu. The SGME model achieved sound results, but with some problems still awaiting solution, including unsustainable funding and obscure rural characteristics. The findings of this study shed light on the planning of similar areas in other developing economies, especially those with a distinct urban-rural dual system. Abstrak. Seiring urbanisasi yang cepat di Tiongkok, sebuah paradoks muncul ketika populasi perdesaan di Cina berkurang, tetapi permukiman di perdesaan masih berkembang dalam bentuk perumahan perdesaan yang telah direnovasi dan bertambahnya lahan konstruksi, terutama di daerah pengirim migran. Sistem ganda perkotaan-perdesaan di Cina disalahkan sebagai penyebab utama fenomena abnormal ini, tetapi karena sistem ganda ini mendasar bagi perkembangan sosial-ekonomi Tiongkok dan pemerintah Pusat Tiongkok mengadopsi reformasi kelembagaan dengan cara selangkah demi selangkah, pemerintah daerah harus mengatasi dua sistem ini. Banyak kota berencana dan menerapkan penyusutan cerdas dari permukiman perdesaan, dan Chengdu adalah salah satu praktik terbaik dalam konteks Cina. Penelitian ini menggambarkan model SGME terbaru (permukiman skala kecil, pengaturan kelompok, pemandangan pastoral mikro dan konstruksi ekologis) yang dimulai pada tahun 2013 untuk mengimplementasikan konsolidasi yang direncanakan dari permukiman perdesaan yang sesuai dengan ideologi pembangunan lokal. Untuk mengalokasikan fasilitas layanan publik dengan lebih baik dan meningkatkan efisiensi pasokan sumber daya, enam mode aglomerasi spasial direncanakan untuk mengkonsolidasikan desa-desa yang tersebar di seluruh Chengdu. Model SGME telah mencapai hasil yang baik namun dengan beberapa masalah menunggu solusi, termasuk dana yang tidak berkelanjutan dan karakteristik perdesaan yang tidak jelas. Temuan-temuan ini akan menjelaskan perencanaan bidang-bidang serupa di negara-negara berkembang lainnya, terutama yang memiliki sistem ganda perkotaan-perdesaan yang berbeda. Kata Kunci. Penyusutan cerdas, konsolidasi pemukiman pedesaan, model SGME, Chengdu, Cina.